Ascending aorta-common hepatic artery bypass for mesenteric revascularization. (2017) - Murakami, Yuri; Toya, Naoki; Fukushima, Soichiro; Ito, Eisaku; Akiba, Tadashi; Ohki, Takao
Highlights: We report the case of a patient who underwent hemodialysis because of a bilateral renal occlusion. He also had occlusion of the superior mesenteric artery and stenosis of the celiac artery. We performed antegrade bypass using great saphenous vein from the ascending aorta to the common hepatic artery. The bypass remained patent 20 months after the procedure, and the patient was asymptomatic. There is no report using the common hepatic artery as a revascularization outflow in patients with CMI. Abstract: Introduction: Chronic aortic occlusion usually occurs from the infrarenal branch to the terminal aorta. We report the case of a patient with an occlusion that began at the suprarenal artery, and there was also occlusion of the superior mesenteric artery and extreme stenosis of the celiac artery. Antegrade bypass from the ascending aorta to the common hepatic artery was performed. Presentation of case: A 59-year-old patient presented to our hospital with uremia due to acute anuric renal failure and anorexia. CT revealed long-segment occlusion of the thoracoabdominal aorta including the superior mesenteric artery and bilateral renal arteries. Additionally, there was high-grade stenosis in the celiac artery. We treated the patient using an antegrade bypass from the ascending aorta to the common hepatic artery. His recovery and postoperative course were uneventful. Antegrade bypass from the ascending aorta is an effective alternative for patients who have visceral ischemia. Discussion: A recent study showed that surgical revascularization for chronic mesenteric ischemia (CMI) provides good midterm patency and mortality. Descending aorta or the common iliac artery is usually used as an inflow. In our patient, we decided to use the ascending aorta to provide more absolute flow, and the CHA was used as an outflow because it was easy to expose. To our knowledge, there is no report of using the CHA as a revascularization outflow for patients with CMI. Conclusion: In an extensively occluded aorta, the ascending aorta is an excellent alternate inflow for revascularization of the mesenteric artery.